2013
DOI: 10.1242/jcs.124438
|View full text |Cite
|
Sign up to set email alerts
|

The GEF Vav regulates guided cell migration by coupling guidance receptor signalling to local Rac activation

Abstract: SummaryGuided cell migration is a key mechanism for cell positioning in morphogenesis. The current model suggests that the spatially controlled activation of receptor tyrosine kinases (RTKs) by guidance cues limits Rac activity at the leading edge, which is crucial for establishing and maintaining polarized cell protrusions at the front. However, little is known about the mechanisms by which RTKs control the local activation of Rac. Here, using a multidisciplinary approach, we identify the GTP exchange factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 42 publications
2
41
0
2
Order By: Relevance
“…S4E,F, Movie 7). These data are consistent with a permanent Rac polarisation signal due to PVR expression (Fernandez-Espartero et al, 2013;Poukkula et al, 2011) and indicate that guidance receptors regulate NMII activity in order to control border cell behaviour. It can be inferred from these data that PVR contributes to inhibition of NMII activity, which prevents rotation in the early phase.…”
Section: Egfr and Pvr Oppositely Control Nmii Activitysupporting
confidence: 83%
“…S4E,F, Movie 7). These data are consistent with a permanent Rac polarisation signal due to PVR expression (Fernandez-Espartero et al, 2013;Poukkula et al, 2011) and indicate that guidance receptors regulate NMII activity in order to control border cell behaviour. It can be inferred from these data that PVR contributes to inhibition of NMII activity, which prevents rotation in the early phase.…”
Section: Egfr and Pvr Oppositely Control Nmii Activitysupporting
confidence: 83%
“…Although the functions of Vav proteins in the nervous system are far from clear, several studies have found critical roles for Vav family members in nervous system function. For example, Vav proteins have been shown to be important for axonal development (Cowan et al 2005;Malartre et al 2010;Sauzeau et al 2010a;Fernandez-Espartero et al 2013), synaptic plasticity (Hale et al 2011), and negative regulation of sympathetic nervous system activity (Sauzeau et al 2006(Sauzeau et al , 2007(Sauzeau et al , 2010b(Sauzeau et al , 2011Zhu et al 2015). Moreover, Vav3 has been identified as a candidate schizophrenia gene (Ikeda et al 2011;Aleksic et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported Rac activity to be polarized at the front of the border cell cluster (Fig. 2 f; Fernández-Espartero et al, 2013;Cai et al, 2014). Importantly, photoactivation of Rac1 in an individual cell of the cluster in vivo is sufficient to reroute migration and inhibit protrusion formation in the surrounding cells, whereas photoactivation of a dominant-negative Rac1 mutant induces multiple protrusions in the clusters, phenocopying loss of RTK function (Wang et al, 2010).…”
Section: Leaders Respond To Guidance Cues and Are Dynamically Establimentioning
confidence: 91%
“…Early studies suggested the small GTPase Rac1, which is essential for lamellipodial protrusion (Ridley et al, 2003), and its GEF, Mbc/ DOCK180, act downstream of PVF-1 ). Furthermore, Rac activity (Murphy and Montell, 1996) and the Rac GEF Vav2 (Fernández-Espartero et al, 2013) are essential for border cell migration. Recent studies have reported Rac activity to be polarized at the front of the border cell cluster (Fig.…”
Section: Leaders Respond To Guidance Cues and Are Dynamically Establimentioning
confidence: 99%